Recent Referees (Journal of Political Economy, 2021)
Previous articleNext article FreeRecent RefereesPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJournal of Political Economy acknowledges the assistance of:Brant AbbottFrancesco AgostinelliDavid AlbouyTreb AllenOmar Al-UbaydliManuel AmadorSandro AmbuehlIsaiah AndrewsJuan Antolin-DiazAndrew AtkesonAdrien AuclertDavid Austen-SmithDavid AutorScott BakerSpencer BanzhafGadi BarlevyChristian BayerAnke BeckerMarianne BertrandManudeep BhullerBarbara BiasiJoaquin BlaumLeah BoustanBen BrooksKevin BryanJulia CageEnrico CantoniAgostino CapponiJean-Paul CarvalhoHector ChadeLaurens CherchyeGabe Chodorow-ReichThomas ColemanDaniele CondorelliJohn ConlonChristopher CostelloGordon DahlEduardo DavilaTommaso DentiMichael DinersteinWill DobbieAntonio Doblas-MadridMatthias DoepkeSebastian DyrdaFlorian EdererMark EganMaximilian EhrlichLasse EikaMatt ElliottWilliam EvansRobert FairlieRoger FarmerShuaizhang FengJesus Fernandez-VillaverdeFilippo FerroniDoireann FitzgeraldMarco FrancesconiPeter FredrikssonChao FuYana GallenGarance GenicotMichael GerusoMichela GiorcelliMikhail GolosovCorbett GraingerPaul GriecoCristina GualdaniGlenn HarrisonJonathan HeathcoteNathaniel HendrenNathan HendricksKevin HooverJean-Francois HoudeCosmin IlutPeter KaradiMelissa KearneyPatrick KehoeTodd KeisterWilliam KerrJudd KesslerNicolas KleinPatrick KlineRalph KoijenFabian KosseAart KraayMatthias KredlerEliana La FerraraLuc LaevenDavid LagakosRicardo LagosMoritz LenelAndrei LevchenkoArthur LewbelXing LiAriel ListoJoan LlullKatrine LokenRocco MacchiavelloAlejandro ManelliRamon MarimonCostas MeghirEnrique MendozaLukas MenkhoffGuido MenzioMargaret MeyerAmeet MorjariaSuresh NaiduSalvador NavarroDavid NovgorodskyPablo OttonelloKrishna PendakurEduardo Perez-RichetWolfgang PesendorferAlessandra PeterGiacomo PonzettoAndrea PratJoseph PriceUday RajanValerie RameyNeel RaoJohn RehbeckPhilip RenyPascual RestrepoGary RichardsonGuillaume RocheteauMark RosenzweigSutanuka RoyJuan Pablo RudJohn RustThomas SampsonSusanne SchennachPaul SchmelzingPetr SedlacekAjay ShenoyXi SongDavid SplinterDmitriy StolyarovWilliam StrangeDavid StrombergBruno StruloviciJan StuhlerRobert SugdenEric SwansonAndrew SweetingSteven TadelisAndrea TambalottiEugene TanOlivier TercieuxAlexander TorgovitskyGerman Villegas BauerJonathan VogelDaniel WilhelmBen WilliamsAlexander WolmanLiangjie WuAli YurukogluGema ZamarroYiyi ZhouJidong Zhou Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 129, Number 1January 2021 Article DOIhttps://doi.org/10.1086/713346 Views: 260 © 2021 by The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.